O zjawisku lęku językowego z perspektywy uczących się drugiego/kolejnego języka obcego online - Półtorak, Ewa (Neofilolog, 2022)
The aim of the paper is to reflect on the problem of language anxiety in the foreign language teaching-learning process. The concept of language anxiety in the online language teaching-learning context is discussed, with particular relation to synchronous communication tools. The context is the learners’ perspective of adult beginners at the university level learning French as a second/subsequent language. The research group included 85 students of the first and second years of French at the University of Silesia in Katowice. To collect the data participants were asked to complete the Foreign Language Classroom Anxiety Scale (FLCAS), developed by Horwitz, Horwitz and Cope (1986), and to respond to six additional questions, related to the online language teaching-learning context. Results showed that language anxiety is a phenomenon that may accompany the regular online teaching-learning process of a second/subsequent foreign language.